The comparison of drug usage in Emergency Department (ED) Pharmacy Hospital Putrajaya (HPJ) and Klinik Kesihatan Putrajaya (KKPJ) - Majid, Norasma; Bakaruddin, Syafi'ah; Syahlan, Syahrina; Che Bahanuddin, Che Asma (2009)
Background and objective: Government hospital's Emergency Department (ED) and Klinik Kesihatan are the most frequent visited by public as a preferred health care provider for health issue. The extensive usage of ED for green zone cases (refer Appendix I) has lead to the setting of ED pharmacy in Hospital Putrajaya (ED HPJ). Despite the existing Klinik Kesihatan Putrajaya (KKPJ) nearby the hospital, green cases in ED keep increasing statistically year by year. Therefore, the objective of this study was to investigate the trend of drug usage in ED HPJ and KKPJ according to pharmacological properties in order to expose which cases are the most prevalent in both setting. This discovery will function to assist in stock handling and arrangement corresponding with 5's concept (refer Appendix 2) applied in all government organization.